GE_GERICHTE C/5527/2014 vom 11. August 2014 - GE Cour de justice (2014)
VENTE; CONTRAT INTERNATIONAL; MESURE PROVISIONNELLE; CONCLUSION DU CONTRAT; COMPÉTENCE RATIONE LOCI | LDIP.118; LDIP.10; CPC.261; CL.5.1.a; CL.5.1.b; CL.31